Costs analysis of municipal solid waste management scenarios: IASI – Romania case study - Ghinea, Cristina; Gavrilescu, Maria (Journal of Environmental Engineering and Landscape Management, 2016)
Effective management of solid waste has become environmentally and economically mandatory due to the increase of environmental problems. In this context, the evaluation of economic aspects is imperative since the implementation of a solid waste management system is connected with considerable investment and operating costs. The goal of this study is to assess and report the performance of various waste management scenarios in terms of costs and to determine the most suitable alternative. For this purpose, we analyzed a case study in a typical Romanian urban area, in terms of the economic impacts of four waste management scenarios. The economic evaluation was performed based on a cost structure, which we have elaborated to analyze the waste management scenarios from a cost perspective. The results indicated that the most suitable alternative for implementation from economic viewpoint in the studied area is scenario which included the following treatment/elimination methods: sorting, composting and landfilling.